Effect of Cr Substitution on Magnetic Properties of Mg Nanoferrites Synthesized by Citrate-Gel Auto Combustion Method - M. Raghasudha; D. Ravinder; P. Veerasomaiah (Journal of Chemistry)
A series of Mg-Cr nanoferrites with the chemical formula MgCrxFe2−xO4 () were synthesized by Citrate-Gel auto combustion method. The formation of single phase cubic spinel structure of the samples was confirmed by X-ray diffraction (XRD) analysis. It is observed that with the increase in the paramagnetic Cr content, the particle size of the ferrite compositions has decreased from 23 nm to 7 nm. Faraday magnetic Susceptibility Balance was used to measure the Magnetic susceptibility of synthesized samples that confirmed the paramagnetic nature of the ferrites. Vibrating Sample Magnetometer (VSM) was used to measure the Magnetic properties of nanoferrites under investigation at room temperature under the applied magnetic field of 15 kOe. With the increase in Cr3+ concentration, the saturation magnetization has decreased from 11 emu/g to 1.5 emu/g.